Pengaruh Budaya Terhadap Perilaku Pengemis Anak Di Kecamatan Kamal-Kab. Bangkalan - Indah Permata Sari; Iriani Ismail (Trunojoyo University of Madura, 2014)
The emergence of the assumption that the birth of the begging culture due to two of the most influential cultures of the children in choosing a profession beggar is culture and family environment. Culture is also able to influence one's attitude and behavior. By the results of research on the influence of culture on behavior of child beggars in Kamal district. Bangkalan can be said to be very alarming. It can be seen from the two variables are variables that culture consists of three indicators to measure a culture that is about perception among ethnographic them as beggars. Socialization is the role of family or environment that causes them to work as beggars. And the modus operandi of the form of beggars or practice of begging, and tissue between the beggars in the village and a variable behavior consists of two indicators, namely behavioral sociology that explain behavior that occurs in the present through the possibility of consequences that occur in the future . The exchange of social teory stating that any or disappointments that occur in human life originated on the behavior of others. Based on the results of the study, there is a behavior that causes disappointment because there are factors or the encouragement of family culture and environment.